Android Based Rosella Tea Sales Application as Digital Innovation - Lusia Septia Eka Esti Rahayu; Marlia Sari; Muhammad Junaidi (Penerbit Goodwood, 2025)
Purpose: This study aims to develop an Android-based sales application for Rosella Tea as a digital innovation, addressing the need for efficient marketing and sales management among Women Farmers Groups (KWT) in East Ambarawa Village, Lampung. Methodology/approach: The research utilizes the System Development Life Cycle (SDLC) method, with stages including needs analysis, system design using Unified Modeling Language (UML), coding with Java, and data storage via Firebase. Results/findings: The developed application successfully operates on Android devices, presenting products informatively and enabling real-time transactions and sales management. It enhances marketing efficiency and expands the market reach for Rosella Tea, improving transaction processes between sellers and buyers. Conlusion: The Android-based application serves as an innovative solution to promote Rosella Tea digitally, offering better sales management, expanding market access, and increasing business efficiency for women farmers. Limitations: The study did not explore the full range of features needed, such as integration with various payment methods and e-commerce platforms. Contribution: The application provides a digital pathway for Women Farmers Groups to manage and promote local products, contributing to their economic empowerment and aligning with government initiatives to support MSMEs' digitalization.